Information resources to aid parental decision-making on when to seek medical care for their acutely sick child: a narrative systematic review. Issue 12 (16th December 2015) - Neill, Sarah; Roland, Damian; Jones, Caroline HD; Thompson, Matthew; Lakhanpaul, Monica
Abstract : Objective: To identify the effectiveness of information resources to help parents decide when to seek medical care for an acutely sick child under 5 years of age, including the identification of factors influencing effectiveness, by systematically reviewing the literature. Methods: 5 databases and 5 websites were systematically searched using a combination of terms on children, parents, education, acute childhood illness. A narrative approach, assessing quality via the Mixed Methods Appraisal Tool, was used due to non-comparable research designs. Results: 22 studies met the inclusion criteria: 9 randomised control trials, 8 non-randomised intervention studies, 2 qualitative descriptive studies, 2 qualitative studies and 1 mixed method study. Consultation frequency (15 studies), knowledge (9 studies), anxiety/reassurance (7 studies), confidence (4 studies) satisfaction (4 studies) and antibiotic prescription (4 studies) were used as measures of effectiveness. Quality of the studies was variable but themes supported information needing to be relevant and comprehensive to enable parents to manage an episode of minor illness Interventions addressing a range of symptoms along with assessment and management of childhood illness, appeared to have the greatest impact on the reported measures. The majority of interventions had limited impact on consultation frequencies, No conclusive evidence can be drawn from studies measuring other outcomes. Conclusions: Findings confirm that information needs to be relevant and comprehensive to enable parents to manage an episode of minor illness. Incomplete information leaves parents still needing to seek help and irrelevant information appears to reduce parents' trust in the intervention. Interventions are more likely to be effective if they are also delivered in non-stressful environments such as the home and are coproduced with parents.